Demodex and the eye – A review - Sumana Chatterjee; Jaya Gupta; Sanjeev P Srinivas; Srinivas K Rao (Indian Journal of Ophthalmology)
Demodex blepharitis (DB) has become one of the common differential diagnoses in patients presenting with red eyes in daily clinics. In this review article, we have incorporated a detailed discussion about the mite and the various mechanisms by which it causes different signs and symptoms, the risk factors, and diagnostic methods with current and emerging treatment modalities. Because of the chronic symptoms and rather a late diagnosis, DB considerably affects patients’ quality of life. The clues to identify cylindrical dandruff, the diagnostic sign of Demodex, visualization of the mite correlating their presence with signs and symptoms, and instituting early and appropriate treatment are the goals of this article.